Instagram as a Media for Presidential Election Campaigns in Indonesia: A Literature Study of the 2024 Presidential Election - Nurhawaeny Kardiyati, Endah; Tri Kartono, Drajat; Irfan, Agus (Jurnal Polisci, 2024)
Instagram is gaining popularity in Indonesia, and its users are millennials; some officials and politicians create Instagram accounts and start actively using it to build personal branding. Personal branding is quite effective in attracting support on social media. Personal branding must be carried out long before the campaign period. After a long time, social media users will begin to trust the image built through personal branding. Here are some things about personal branding for political campaigns. The method used in this study is a literature review related to the use of Instagram media for campaigns in the Presidential and Vice Presidential Candidate Elections. Data was obtained from the internet, social media, and journal articles. The 2024 Presidential Election is a presidential election that uses social media to convey their ideas and ideas. One of the vast users is Instagram. The difference in the effectiveness of the Instagram application in campaigns still needs to be tested further. However, Instagram social media can be an effective means of political socialization by selecting information and digital literacy, especially in responding to various political discourses and issues related to the 2024 Presidential Election